Ultrastructural and biochemical analyses reveal cell wall remodelling in lichen-forming microalgae submitted to cyclic desiccation–rehydration - González-Hourcade, María; Braga, Marcia R; del Campo, Eva M; Ascaso, Carmen; Patiño, Cristina; Casano, Leonardo M (Annals of botany, 2020)
One of the most distinctive features of desiccation-tolerant plants is their high cell wall (CW) flexibility. Most lichen microalgae can tolerate drastic dehydration-rehydration (D/R) conditions; however, their mechanisms of D/R tolerance are scarcely understood. We tested the hypothesis that D/R-tolerant microalgae would have flexible CWs due to species-specific CW ultrastructure and biochemical composition, which could be remodelled by exposure to cyclic D/R. Two lichen microalgae, Trebouxia sp. TR9 (TR9, adapted to rapid D/R cycles) and Coccomyxa simplex (Csol, adapted to seasonal dry periods) were exposed to no or four cycles of desiccation [25-30 % RH (TR9) or 55-60 % RH (Csol)] and 16 h of rehydration (100 % RH). Low-temperature SEM, environmental SEM and freeze-substitution TEM were employed to visualize structural alterations induced by D/R. In addition, CWs were extracted and sequentially fractionated with hot water and KOH, and the gel permeation profile of polysaccharides was analysed in each fraction. The glycosyl composition and linkage of the main polysaccharides of each CW fraction were analysed by GC-MS. All ultrastructural analyses consistently showed that desiccation caused progressive cell shrinkage and deformation in both microalgae, which could be rapidly reversed when water availability increased. Notably, the plasma membrane of TR9 and Csol remained in close contact with the deformed CW. Exposure to D/R strongly altered the size distribution of TR9 hot-water-soluble polysaccharides, composed mainly of a β-3-linked rhamnogalactofuranan and Csol KOH-soluble β-glucans. Cyclic D/R induces biochemical remodelling of the CW that could increase CW flexibility, allowing regulated shrinkage and expansion of D/R-tolerant microalgae.